Mutation in HvCBP20 (Cap Binding Protein 20) Adapts Barley to Drought Stress at Phenotypic and Transcriptomic Levels - Daszkowska-Golec, Agata; Skubacz, Anna; Marzec, Marek; Slota, Michal; Kurowska, Marzena; Gajecka, Monika; Gajewska, Patrycja; Płociniczak, Tomasz; Sitko, Krzysztof; Pacak, Andrzej; Szweykowska-Kulinska, Zofia; Szarejko, Iwona (Frontiers in Plant Science, 2017)
CBP20 (Cap-Binding Protein 20) encodes a small subunit of the cap-binding complex (CBC), which is involved in the conserved cell processes related to RNA metabolism in plants and, simultaneously, engaged in the signaling network of drought response, which is dependent on ABA. Here, we report the enhanced tolerance to drought stress of barley mutant in the HvCBP20 gene manifested at the morphological, physiological, and transcriptomic levels. Physiological analyses revealed differences between the hvcbp20.ab mutant and its WT in response to a water deficiency. The mutant exhibited a higher relative water content (RWC), a lower stomatal conductance and changed epidermal pattern compared to the WT after drought stress. Transcriptome analysis using the Agilent Barley Microarray integrated with observed phenotypic traits allowed to conclude that the hvcbp20.ab mutant exhibited better fitness to stress conditions by its much more efficient and earlier activation of stress-preventing mechanisms. The network hubs involved in the adjustment of hvcbp20.ab mutant to the drought conditions were proposed. These results enabled to make a significant progress in understanding the role of CBP20 in the drought stress response.